Usage of pedestrian bridge among the urban commuters in Kuala Lumpur - Wahab, Siti Norida; Lay, Yan Feng; Koay, Wui Lim; Amir Hussin, Amir 'Aatieff (EDP Sciences, 2020)
Pedestrian bridges are one of the safest crossing facilities, allowing pedestrians to cross the road by diverting away from traffic. However, the usage of pedestrian bridges has not been popular in Malaysia. Dreadful conditions of pedestrian bridges further contribute to the low usage. The main aim of this research is to develop a conceptual model to identify the motivating factors affecting the usage of pedestrian bridges among urban commuters in Kuala Lumpur. Four factors were identified from an extensive review of literature to construct the model namely safety, attitude, facilities and convenience. This study serves valuable information for scholar to further study and analyse topic relating to the use of pedestrian bridges. From the practitioner’s point of view, this study provides valuable information to policy makers and government authorities to integrate and focus on the most motivating factors that could attract more users into utilising pedestrian bridges.